The beggars' Bible - Vernon, Louise A.; McCoy, Jeanie (Scottdale, Pa., Herald Press, 1971)
In fourteenth-century England a poor boy becomes a disciple of John Wycliffe and helps spread word of his English translation of the Bible.
Keywords: Wycliffe, John, -- -1384 -- Juvenile fiction; Wycliffe, John, -- d. 1384 -- Fiction